2019
DOI: 10.1002/ajmg.a.61432
|View full text |Cite
|
Sign up to set email alerts
|

Primrose syndrome associated with unclassified immunodeficiency and a novel ZBTB20 mutation

Abstract: Primrose syndrome is a congenital malformation syndrome characterized by intellectual disability, developmental delay, progressive muscle wasting, and ear lobe calcification. Mutations in the ZBTB20 gene have been established as being accountable for this syndrome. In this study, a novel de novo ZBTB20 mutation, NM_001164342.2:c.1945C>T (p.Leu649Phe), has been identified through whole exome sequencing (WES) in a female patient presenting a typical Primrose phenotype. Because the present patient exhibited recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Here we have performed additional linkage analyses as well as whole exome, whole genome, and Sanger sequencing, which revealed a unique rare homozygous coding variant in ZBTB20 (MIM: 606025) that co-segregates with stuttering in this family. Although no individuals with homozygous mutations in ZBTB20 have previously been observed, heterozygous mutations have been associated with Primrose syndrome, a rare multisystem developmental disorder [14,15,16,17,18,19,20,21,22,23]. ZBTB20, also known as DPZF [24], HOF [25], or ZNF288 is a member of the POK (POZ and Krüppel) family of transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…Here we have performed additional linkage analyses as well as whole exome, whole genome, and Sanger sequencing, which revealed a unique rare homozygous coding variant in ZBTB20 (MIM: 606025) that co-segregates with stuttering in this family. Although no individuals with homozygous mutations in ZBTB20 have previously been observed, heterozygous mutations have been associated with Primrose syndrome, a rare multisystem developmental disorder [14,15,16,17,18,19,20,21,22,23]. ZBTB20, also known as DPZF [24], HOF [25], or ZNF288 is a member of the POK (POZ and Krüppel) family of transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…Alpha‐fetoprotein (AFP) levels showed that levels were typically elevated but not in all affected individuals, and did not show a marked change over time (Figure 2C). One patient showed selective IgG2 deficiency (P31) 18 . One patient developed a testis carcinoma at 27 years and a (fatal) seminoma in the other testis at 40 years of age 5 Another male developed a germ cell tumor at 28 years and also a seminoma at that age 9…”
Section: Resultsmentioning
confidence: 99%
“…No biochemical or genetic studies were performed specifically for the present study. We gathered data from 29 patients reported previously 1‐18 and 13 hitherto unpublished patients. One stillbirth was also included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ZBTB20 , located at 3q13.31, has been identified as the causative gene for Primrose syndrome (MIM #259050), which is associated with severe neurodevelopmental disorders [ 30 ]. Previously, we found that the symptoms associated with neurodevelopmental disorders were very mild and inconsistent in the cases with 3q13 deletion compared to those observed in Primrose syndrome [ 31 ].…”
Section: Genes Whose Phenotypes Are Not Affected By Genomic Copy Number Changesmentioning
confidence: 99%